A Study of Decision Support System on Renewable Energy: Analyzing Renewable Energy Policies and Regulations in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The aim of this paper is to provide renewable energy sources with the future of the energyindustry, and it is through supportive and extensive legislation covering all possible aspects of theenergy sector that these revolutions should be regulated. The government's decision to expand itsconsumption of renewable energy should be effectively implemented. In this study, the existingrenewable energy legislation and regulations mechanism in India is analyzed and the barriers andchallenges to the renewable energy industry are examined. A benchmark study of the best policies andlegislations for renewable energies adopted by different countries is therefore included in this thesis,which will help shape India's effective policy. In addition, there is no single comprehensive renewableenergy policy statement in the country. Policies were developed to support the growth of specifictechnologies in the field of renewable energy. The renewable energy sector development plansformulated in the past do not correspond to current policies and initiatives. Whereas the RenewableEnergy capacity increase of MNRE is not sufficient to meet the RE Generation Objective, which ismandated under the Jawaharlal Nehru National Solar Mission (JNNSM) (NAPCC).